Penguatan karakter rasa ingin tahu dan peduli sosial melalui discovery learning - Achmad Fauzi; Zainuddin Zainuddin; Rosyid Atok (Universitas Negeri Malang, 2017)
Efforts to strengthen the character become the basis in the implementation of the curriculum 2013. Application of the 2013 curriculum provides a paradigm shift, which in the end result of learning students not only master the knowledge but also master the attitude and skills. One of the two characters developed is curiosity and social care. To form the character, it needs an educational instrument such as a competent teacher, adequate learning resources, and the most important is the action of learning in the form of approach, model, method, or appropriate learning strategy. So the application of discovery learning model with scientific approach. Which model is effective and efficient in bring up the character of curiosity and social care. KeywordsCuriosity, Social Care, Discovery Learning http://dx.doi.org/10.17977/um022v2i22017p079